Kon cepcja rado ści w SumIE TeologiI św. To masza z Akwinu - Płotka, Magdalena (Studia Theologica Varsaviensia, 2019)
The purpose of this article is to present the development of Thomas Aquinas’s concept of joy in the subsequent parts of Summa theologiae. Beginning with the description of joy as simple movements of the soul, Thomas comes to present the concept of spiritual joy, which is fundamental to the human visio beatifica. Therefore, the article is divided into three parts, which discuss Aquinas’s accounts of joy: Prima secundae, Secunda secundae and Tertia pars. The first part focuses on the inclusion of joy as experience and feeling. Joy here is understood as one of the feelings of the sensitive power is considered in the perspective of human emotionality (vis concupiscibilis). Joy that comes from satisfying the lack of sensory goods is called pleasure (delectatio). It differs from the joy of affection (gaudium) – the intellectual and spiritual affrct, to which the second part of the article is dedicated. Spiritual joy does not include the sensory-corporal component, and it superimposes itself over purely intelligible beings. Thomas clearly emphasizes that only God can be the cause of spiritual joy. This perspective allows Aquinas to develop his concept of theology of joy in the next part of Summa (III pars), which is devoted in the last part of this text. The emotionality of Christ is the central problem for Thomas here. These considerations throw a lot of light not only on the supernatural approach to joy, but also on the ways in which joy – the fruit of the Holy Spirit can be experienced by a human being in hac via.